Non-vitamin K antagonist oral anticoagulants (NOACs) for thromboembolic prevention, are they safe in congenital heart disease? Results of a worldwide study. (15th January 2020) - Yang, H.; Bouma, B.J.; Dimopoulos, K.; Khairy, P.; Ladouceur, M.; Niwa, K.; Greutmann, M.; Schwerzmann, M.; Egbe, A.; Scognamiglio, G.; Budts, W.; Veldtman, G.; et al.
Abstract: Background: Current guidelines consider vitamin K antagonists (VKA) the oral anticoagulant agents of choice in adults with atrial arrhythmias (AA) and moderate or complex forms of congenital heart disease, significant valvular lesions, or bioprosthetic valves, pending safety data on non-VKA oral anticoagulants (NOACs). Therefore, the international NOTE registry was initiated to assess safety, change in adherence and quality of life (QoL) associated with NOACs in adults with congenital heart disease (ACHD). Methods: An international multicenter prospective study of NOACs in ACHD was established. Follow-up occurred at 6 months and yearly thereafter. Primary endpoints were thromboembolism and major bleeding. Secondary endpoints included minor bleeding, change in therapy adherence (≥80% medication refill rate, ≥6 out of 8 on Morisky-8 questionnaire) and QoL (SF-36 questionnaire). Results: In total, 530 ACHD patients (mean age 47 SD 15 years; 55% male) with predominantly moderate or complex defects (85%), significant valvular lesions (46%) and/or bioprosthetic valves (11%) using NOACs (rivaroxaban 43%; apixaban 39%; dabigatran 12%; edoxaban 7%) were enrolled. The most common indication was AA (91%). Over a median follow-up of 1.0 [IQR 0.0–2.0] year, thromboembolic event rate was 1.0% [95%CI 0.4–2.0] (n = 6) per year, with 1.1% [95%CI 0.5–2.2] (n = 7) annualized rate of major bleeding and 6.3% [95%CI 4.5–8.5] (n = 37) annualized rate of minor bleeding. Adherence was sufficient during 2 years follow-up in 80–93% of patients. At 1-year follow-up, among the subset of previous VKA-users who completed the survey (n = 33), QoL improved in 6 out of 8 domains ( p  ≪ 0.05). Conclusions: Initial results from our worldwide prospective study suggest that NOACs are safe and may be effective for thromboembolic prevention in adults with heterogeneous forms of congenital heart disease. Highlights: Up until now, no data are available on NOACs in ACHD patients with atrial arrhythmia. NOACs appear to be safe during short-term use in ACHD with moderate-complex defects. This may also apply to ACHD patients with valvular disease or bioprosthetic valves. Future OAC recommendations in ACHD should consider this international experience.